2021
DOI: 10.3390/catal11081004
|View full text |Cite
|
Sign up to set email alerts
|

Organocatalysis for the Asymmetric Michael Addition of Cycloketones and α, β-Unsaturated Nitroalkenes

Abstract: Michael addition is one of the most important carbon–carbon bond formation reactions. In this study, an (R, R)-1,2-diphenylethylenediamine (DPEN)-based thiourea organocatalyst was applied to the asymmetric Michael addition of nitroalkenes and cycloketones to produce a chiral product. The primary amine moiety in DPEN reacts with the ketone to form an enamine and is activated through the hydrogen bond formation between the nitro group in the α, β-unsaturated nitroalkene and thiourea. Here, the aim was to obtain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…The study on the reaction mechanism according to the type of configurational diastereomers [37] and the reactivity of each solvent was verified through quantum calculation. In addition, the effect of the fluorine substituent on the organic catalyst 1b confirmed in the previous study was confirmed in more depth [33,34]. To investigate the effect of the catalyst on the enantioselective Michael addition of aldehydes and nitroalkynes, the reaction was performed using isobutyraldehyde and trans-beta-nitrostyrene.…”
Section: Introductionmentioning
confidence: 56%
See 3 more Smart Citations
“…The study on the reaction mechanism according to the type of configurational diastereomers [37] and the reactivity of each solvent was verified through quantum calculation. In addition, the effect of the fluorine substituent on the organic catalyst 1b confirmed in the previous study was confirmed in more depth [33,34]. To investigate the effect of the catalyst on the enantioselective Michael addition of aldehydes and nitroalkynes, the reaction was performed using isobutyraldehyde and trans-beta-nitrostyrene.…”
Section: Introductionmentioning
confidence: 56%
“…The relative free and thermal energies of the solvent effect for the Michael reaction steps are shown in Figure 5 through DFT calculations. We observed that the Michael addition reaction can be accelerated due to the hydrophobicity of thiourea-DPEN-based fluorine-substituted organic catalysts used in a previous study [32,33]. Furthermore, the hydrogen bonding between the nitro group of the nitroalkene and the thiourea of the catalyst causes the aromatic substituents on the alkene to be positioned like those in TS1 and TS2 with relatively lower steric hindrance.…”
Section: Reaction Mechanism Inferred Through Expected Transition Statesmentioning
confidence: 79%
See 2 more Smart Citations
“…[1][2][3][4][5][6][7] In particular, the conjugate addition of 1,3-dicarbonyl compounds to trans-β-nitrostyrenes has attracted particular interest due to the reactivity of the resulting enantiopure products which are key intermediates for the preparation of a large number of pharmaceutical compounds. The asymmetric control of this reaction has been achieved with organocatalysts such as diamines, [8][9][10][11][12][13][14] amine-thioureas, [15][16][17][18][19][20] and Cinchona derivatives. [21][22][23][24][25][26][27][28][29] Therefore, the development of chiral bifunctional hydrogen-bonding organocatalysts, which can activate nucleophiles and electrophiles at the same time, have emerged as powerful organocatalysts.…”
Section: Introductionmentioning
confidence: 99%